Algorithm design for data communications in duty-cycled wireless sensor networks : a survey - Liu, Yang (2013)
Although duty-cycling has long been a critical mechanism for energy conservation in wireless sensor networks, it is only recently that research efforts have been put to design data communication protocols that perform efficiently in duty-cycled wireless sensor networks (DC-WSNs). In this article, we survey these research problems, aiming at revealing insights into the following three key questions: what are the meaningful (algorithm design) problems for DC-WSNs, which problems have been studied and which have not, and what are the essential techniques behind the existing solutions? All these insights may serve as motivations and inspirations for further developments in this field.